HUBUNGAN INISIASI MENYUSUI DINI DENGAN PERCEPATAN INVOLUSI UTERI - Raden Maria Veronika Widiatrilupi; Anik Purwati (JOMIS (Journal of Midwifery Science), 2022)
Uterine involution is one of the important indicators in seeing the mother's recovery during the puerperium, giving early initiation of breastfeeding is believed to accelerate uterine involution. The purpose of this study was to describe the relationship between early initiation of breastfeeding and accelerated uterine involution, identify the success of early initiation of breastfeeding and analyze the effect of early initiation of breastfeeding on uterine involution in postpartum. This study is a pre-experimental research design with static Group Comparison/Posttest Only Control Group Designs conducted in April-May 2021. With a population of all postpartum mothers who breastfeed their babies through baby sucking at the Kartika Husada Donomulyo clinic. The sampling technique used in this study was purposive sampling which met the criteria for spontaneous/normal delivery, while infants with asphyxia, postpartum mothers with bleeding and multiparous mothers were not included in this study. The sample size is 56 postpartum mothers. Which is divided into 2 groups, group A; who initiate early breastfeeding, group B; not initiate early breastfeeding. The results of the study using Chi-Square, there is a P value of 0.00 <0.05, it can be concluded that early breastfeeding initiation has an effect of 13.80 times on the acceleration of uterine involution.